Analisis Keseimbangan Lini Produksi Menggunakan Metode Ranked Positional Weight (Studi Kasus: UD. XYZ) - Imara Hany Anindita; Herlina Herlina (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
UD. XYZ is a company engaged in the production of flooring, lambersering, and decking products. This study was conducted due to the company's inability to consistently achieve production targets and the existence of workload imbalances along the production line. These conditions are indicated by bottlenecks at several production processes, idle time, and the accumulation of work in process (WIP), which negatively affect operational efficiency. The objective of this research is to analyze and develop improvements to production line balancing using the Ranked Positional Weight (RPW) method. Data were collected through direct field observations, including work time measurements for each work element, data adequacy testing, and data uniformity testing. The results show that the implementation of the RPW method reduced the number of workstations from five to three, increased line efficiency from 45.64% to 92.85%, and decreased balance delay from 54.36% to 7.15%. Therefore, the RPW method can be considered an effective alternative for improving line balance and production efficiency in the wood processing industry.